Estimation of salivary biomarkers in passive smoking children - a comparative study (Bangladesh Journal of Medical Science, 2016)
Objective: To evaluate the relationship between passive smoking and salivary biomarkers like pH, buffering capacity and flow rate, sialic acid and amylase levels in children who were passive smokers and compare with the control group. Materials and Methods: Fifty children with history of passive smoking and 50 healthy age matched controls were included in the study. Details on smoking habits of household members, childs dental and dietary habits were collected using a proforma. Saliva samples were collected from both the groups and salivary analysis was done for pH, buffering capacity, flow rate, sialic acid levels and amylase levels. Results: The results of the study showed a lower salivary pH and flow rate with an increase in amylase activity and buffering capacity in passive smoking children when compared to healthy controls. However, sialic acid levels did not show significant differences between passive smoking children and control group.Conclusion: Passive smoking may reduce the protective properties of saliva which can further affect the oral health status of young children and any factor that influences the secretion rate or composition of saliva will ultimately influence caries susceptibility.Bangladesh Journal of Medical Science Vol.15(2) 2016 p.160-165